Tingkatan Resistensi Individu Terhadap Perubahan Dalam Pengembangan Organisasi Di SDN 04 2×11 Kayutanam - Ilham Rafi (CV. ITTC INDONESIA, 2026)
This study aims to analyze the levels of individual resistance to change in organizational development at SDN 04 2×11 Kayutanam. Organizational change in schools is an essential process to improve educational quality; however, it often encounters obstacles in the form of resistance from school members. This research employed a descriptive approach using a survey method. The research subjects consisted of teachers and administrative staff at SDN 04 2×11 Kayutanam. Data were collected through questionnaires and observations and analyzed using descriptive quantitative techniques. The results indicate that the level of individual resistance to change is categorized as moderate, with variations influenced by work experience, understanding of change objectives, and managerial support from school leadership. These findings highlight the importance of effective leadership and organizational communication in reducing resistance and supporting successful school organizational development.